Setting the economy free: privatisation and commercialisation in Nigeria (Lagos: Kee kommunications limited, 1988)
This book examine the role of privatization and commercialization program under the Ibrahim Babangida military administration. The paper further presents the effects of the military on private sector economy.
asm; 05/03/19
Loans
Keywords: Government business enterprise; Economic conditions; Structural adjustment programme; Privatisation; Nigeria